Evaluation of the Maintainability Aspect of Industry 4.0 Service-oriented Production - Esper, Khalil; Schnicke, Frank (IEEE International Conference on Industry 4.0, Artificial Intelligence, and Communications Technology (IAICT), 2020)
Current markets are characterized by rapid changing in requirements and new customer needs. Thus, fast changeable production is a fundamental goal of Industry 4.0 scheme, which aims to make the manufacturing more changeable and efficient by interconnecting the various factory components, and representing the factory assets virtually in digital twins.In order to study the Industry 4.0 changeability capability, we apply scenario-based evaluation. We derive three change scenarios that can be observed in a plant: Change of product flow depending on quality, depending on product type and the introduction of a new product. Using these scenarios, we compare between the third industrial revolution (Industry 3) and Industry 4.0 architectures based on the resultant change impact.For our evaluation, we utilize the Architecture-Level Modifiability Analysis (ALMA) method and describe its instantiation to the given context, providing ALMA 4.0, a guideline for Industry 4.0 Maintainability scenario-based evaluation. The result shows that the change impact on Industry 4.0 is less than Industry 3. Thus, we provide quantitative evidence that changing Industry 4.0 architecture incurs less efforts than Industry 3 change
Keywords: Industrie 4.0; Industry 4.0; industry 3; service-oriented production; changeability; architecture evaluation; maintainability; modifiability; scenario-based evaluation